Maternal pneumococcal endometritis may cause early-onset neonatal sepsis - Pace, Julio; Bonofiglio, Laura; Moral, Laura Lopez; Badia, Marcela; Lachener, Debora; Regueira, Mabel; Mollerach, Marta (Journal of Pediatric Infectious Diseases, 2007)
Streptococcus pneumoniae is a rarely recognized cause of neonatal sepsis. A case of early-onset neonatal sepsis due to penicillin susceptible pneumococci and maternal endometritis is herein described. A male infant was born at 33 weeks of gestation. The baby developed S. pneumoniae bacteraemia and recovered completely following treatment with antibiotics. Four days after partum, the mother was readmitted with fever. S. pneumoniae was recovered from an endometrial sample. Isolates from mother and child were both serogroup 1 and confirmed to be identical on the basis of BOX-polymerase chain reaction typing and pulse-field gel electrophoresis. Perinatal transmission of S. pneumoniae had probably occurred due to ascending infection from the maternal genital tract.
Keywords: Streptococcus pneumoniae; neonatal sepsis; box-typing; pulsed-field gel electrophoresis; endometritis